An ethnography study on mathematical terminologies within two indigenous Makian languages in North Maluku - Dana Arif Lukmana; Mujahid Taha (International Journal of Trends in Mathematics Education Research, 2022)
The two indigenous Makian languages, Western Makian (Makian Luar) and Eastern Makian (Makian Dalam/Taba), stem from two different language families in North Maluku. The indigenous Makian people are typically ignorant of the riches of values and knowledge reserved in their language and culture, including mathematical content. Therefore, through an ethnography approach, this study identifies mathematical terminologies (natural numbers, fractions, number operations, indefinite quantifiers and adverbs of time) that exist in indigenous Makian languages. Data Collecting was conducted through in-depth interviews with indigenous community leaders and some primary literature reviews, then analyzed qualitatively. The mathematical language that has been identified along with the context of its use can be a good entry point and a mean-ingful material in integrating indigenous languages and cultures in mathematics learning.